SUATU TINJAUAN TINDAK PIDANA TRANSAKSI ELEKTRONIK PERBANKAN DALAM UNDANG – UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Ari Affandy (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTAlong with the development of the times, the sophistication of the technology and information was also developed to present any form of convenience and as supporting the needs of human life.One of them in banking that has been used as a supporting technological sophistication and as a form of improved services to their Clients Bank.At this day and age we no longer need to queue up at the bank if it is only to take money out of our savings with the amount that is not too big, we just need to ATM (Automatic Teller Machine) and we could get some money that we need.But with the convenience provided by the Bank on the other hand appeared also a new problem which is a technology-based crimes in a way to break into an ATM machine (Automatic Teller Machine) mode with, among others, credit card fraud, ATM card cloning, by searching for Personal Identification Number (PIN), put a small camera (spycamera) and card reader on an ATM machine, a crime in electronic transactions is constantly evolving in line with technological advances that increasingly sophisticated.In this case whether the legislation  Act No. 11 of 2008 on Information and Electronic Transactions have been made to regulate the problems of information and electronic transactions can be used to catch the perpetrators of these crimesKeywords:Crime, Transaction, Technology, Electronik, Banking